STUDY OF IN VITRO ANTI-LITHIATIC EFFECT OF IPOMOEA BATATAS (L) LEAVES AND TUBEROUS ROOTS - R, Sathish; G, Jeyabalan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study was to demonstrate the in vitro anti-lithiatic effect of Ipomoea batatas (Convolvulaceae) leaves and tuberous roots. Methods: The obtained ethanolic extract of I. batatas leaves and tuberous roots (EIBL and EIBR) and aqueous extract of I. batatas leaves and roots (AIBL and AIBR) were used for this in vitro study. The dissolution method of calcium oxalate by titrimetry method and calcium phosphate by colorimetric method was studied. Nucleation and aggregation of calcium oxalate crystals were determined by a spectrophotometric assay. Results: In the estimation of calcium oxalate by titrimetry method, the I. batatas leaves and roots have very significant (p<0.01) capability to dissolve calcium oxalate. Percentage dissolution of calcium oxalate crystals was found to be 37.53%, 22.74%, 39.74%, and 24.28% for EIBL, AIBL, EIBR, and AIBR, respectively. In the estimation of calcium phosphate by colorimetric method, the percentage dissolution of calcium phosphate crystals by EIBL, AIBL, EIBR, and AIBR was found to be 67.15%, 43.17%, 76.74%, and 47.96%, respectively. The I. batatas leaves and roots were significantly (p<0.01) dissolved calcium phosphate also. The results were clearly shown that I. batatas extracts significantly (p<0.01) inhibited both nucleation and aggregation of calcium oxalate crystals by concentration-dependent manner. The maximum percent inhibition of calcium oxalate nucleation by EIBL, AIBL, EIBR, and AIBR was found to be 59.09%, 50.0%, 84.09%, and 47.73%, respectively, at 1000 Î¼g/ml. The EIBL, AIBL, EIBR, and AIBR were inhibited calcium oxalate aggregation by 63.46%, 36.54%, 84.61%, and 42.3%, respectively, at 1000 Î¼g/ml. Conclusions: The results clearly indicate that I. batatas leaves and tuberous roots were found to express in vitro anti-lithiatic potential.